Socialization and Evaluation of The Level of Compliance of Tuberculosis Patients to The Use Anti-Tuberculosis Drugs to Pharmacy Students of The Lubuk Pakam Medical Health Institute in 2023 - Marbun, Romauli Anna; Sinaga, Falentina; Maharani, Anisa; Sihombing, Yanna Rotua; Anggraeni, Ratih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The incidence of Tuberculosis (TB) is a health issue that must be paid attention to, especially at the Limapuluh Community Health Center. This health center is a health service center in the Fifty District which experiences a high incidence of TB, with the number of TB cases in 2022 increasing from the previous year. The level of patient compliance with treatment is one of the determining factors for the success of therapy. This study aims to provide an understanding of the factors that influence the level of compliance of TB patients with the use of Anti-Tuberculosis Drugs (OAT) at the Limapuluh Community Health Center. The method of service carried out is in the form of communication, information and education related to the use of Anti-Tuberculosis Drugs. The socialization was carried out online through a zoom meeting with the presentation of material and continued with a pretest and posttest as a measuring tool regarding the increase in participants' understanding of the material presented. This activity was carried out on January 06, 2024 at 10.00-12.00 WIB. The results of this service are the counseling material provided to students seen from the posttest results which show that the understanding and increase in knowledge of the participants is good compared to the results of the previous pretest points. In conclusion, students who take part in this activity can further explore the factors that affect patient compliance in taking OAT drugs so that similar activities can be carried out regularly to prevent errors in the use of Anti Tuberculosis drugs.